2021
DOI: 10.1186/s13018-021-02448-9
|View full text |Cite
|
Sign up to set email alerts
|

Muscle pedicle bone flap transplantation for treating femoral neck fracture in adults: a systematic review

Abstract: Background This systematic review was conducted to gather available evidence on the effectiveness of muscle pedicle bone flap transplantation in adult patients with femoral neck fractures. Methods Databases such as PubMed, EMBASE, IEEE, Web of Science, and Cochrane library were searched from their dates of inception until March 2021. Two reviewers independently selected the interventional studies on the assessment of the effectiveness of muscle ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Moreover, due to the rapid development of social economy, high-energy injuries caused by car accidents and falls from height are increasing, and the incidence of femoral neck fractures in young and middle-aged people is increasing year by year [ 4 ]. Young and middle-aged patients require joint function activities, so it is necessary to maintain the shape and function of the original joint through reduction as much as possible [ 5 , 6 ]. One study showed that the incidence of postoperative femoral head necrosis was 16% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, due to the rapid development of social economy, high-energy injuries caused by car accidents and falls from height are increasing, and the incidence of femoral neck fractures in young and middle-aged people is increasing year by year [ 4 ]. Young and middle-aged patients require joint function activities, so it is necessary to maintain the shape and function of the original joint through reduction as much as possible [ 5 , 6 ]. One study showed that the incidence of postoperative femoral head necrosis was 16% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%